Recent Progress on Block-Based Motion Estimation Techniques - Parmar, Nidhi Kunal; Sunwoo, Myung Hoon (Technical review - IETE, 2015)
Motion estimation (ME) has become a bottleneck in many real-time video coding schemes owing to its computation complexity. Thus, fast ME algorithms have become crucial in video encoder design. Because of its simplicity, block-matching ME is the most popular and widely used algorithm. This paper presents a review of recently proposed block-matching ME algorithms. The main concepts of fast ME algorithms can be classified into four categories: reduction in search points, matching criteria, early termination conditions, and multi-resolution approaches. In addition, the pros and cons of the representative algorithms are analysed. Finally, the algorithms are evaluated on the basis of visual quality and number of search points.